The Cytotoxicity and Anti-Inflammatory Properties of 1’s-1’-Acetoxychavicol Acetate (Aca) on Oral Cells - Nur Umairah Atiqah Sabri; Nor Syazwani Muhammad Zahida; Zulfahmi Said; Siti Noor Adnalizawati Adnan; Normaliza Ab Malik (Journal of Dentistry Indonesia, 2026)
Non-Indexed Publication